(untitled) (Revista Logos Ciencia & Tecnología, 2018)
The applied mathematics are the Science who let the development that engineering has reached; however, solving problems had been the headache for students, due to the lack of virtual environments that let the development of concepts, skills, and procedures. The project aims to describe the application of different types of knowledge in problems resolutions of doubles integrals in students who make use of mathematic software in comparison to the traditional teaching. The labor had as a reference the theory of two stadiums translation and solution to solve problems according to Mayer. The investigation was quasi-experimental type. Is highlighted in the results difficulties in the translation phase because it showed a lower level toward the lecture comprehension, specifically of mathematic language in the students; although it evidenced that the 18% of students who approved the exam “pretest”, while the 69% approved the exam “posttest”; It concludes about the importance of use of the mathematic software in the learning of vectoral calculus towards the problems resolution with double integrals; although, it reflected a positive change of the student by developing the activities with the use of the software.